IMPACT OF LAHAR DISASTERS ON STUDENTS’ SELF-AWARENESS AT SMK NEGERI 1 SALAM, MAGELANG REGENCY - Ayu Dila Putri Yuliani; Ratih Puspita Dewi (Universitas Sebelas Maret (UNS), 2024)
Indonesia is located in the subduction zone of three world tectonic plates, so it is prone to several natural disasters, including the eruption of the Merapi Volcano in Magelang Regency. The main threats are hot clouds, volcanic dust, and floods of Lahar. SMK Negeri 1 Salam, as one of the schools in prone areas, needs to be prepared to face these threats, this study aimed to analyze the effect of the experience of Lahar disasters on the self-awareness of students at SMK Negeri 1 Salam, Magelang Regency. A quantitative approach with a correlational design was used in this study. The research sample was students of SMK Negeri 1 Salam as many as 310 students were selected using the Slovin formula. Data was collected through questionnaires consisting of the two main variables namely Lahar disaster experience and self-awareness. Data analysis using Pearson product-moment correlation test and prerequisite test. Disaster experience is evaluated through three indicators: direct experience, characteristics of the disaster, and preparedness to deal with it. The results showed significant experience, especially in understanding the characteristics of disasters, but the level of awareness of learners was in the moderate category. These findings highlight the need for more attention to understanding the actions needed in the event of a disaster. Thus, increasing awareness and preparedness of learners against disasters needs to be considered in the development of disaster education programs.